Women, Business and the Law 2010 : Measuring Legal Gender Parity for Entrepreneurs and Workers in 128 Economies - World Bank (Washington, DC, 2014)
This report presents indicators based on laws and regulations affecting women's prospects as entrepreneurs and employees. Several of these indicators draw on the Gender Law Library, a collection of over 2,000 legal provisions impacting women's economic status. Both resources can inform research and policy discussions on how to improve women's economic opportunities and outcomes. The six indicators of gender differences in formal laws and institutions established in this report include: 1) accessing institutions, 2 ) using prpoerty, 3) getting a job, 4) dealing with taxes, 5) building credit, and 6) going to court. The first 3 indicators (accessing institutions, using property, and getting a job) capture laws that have direct gender dimensions and are based on a reading of such laws from the perspective of individual women. The 4th indicator (dealing with taxes) examines the direct and indirect gender implications of tax policy from the perspective of 4 standardized families with varying tax liabilities. The last 2 indicators (building credit and going to court) examine the ease of access to credit bureaus and courts to examine the indirect effects that microfinance institutions and dispute resolution have on women, who are more likely to rely on nontraditional financial services.